2000
DOI: 10.1095/biolreprod63.4.1185
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Spermatogonial Depletion (jsd) Mutant Seminiferous Tubules Are Capable of Supporting Transplanted Spermatogenesis1

Abstract: In mice, the juvenile spermatogonial depletion (jsd) mutation results in a single wave of spermatogenesis followed by failure of type A spermatogonial stem cells to repopulate the testis, rendering male animals sterile. It is not clear whether the defect in jsd resides in a failure of the somatic component to support spermatogenesis or in a failure that is intrinsic to the mutant's germ cells. To determine if the jsd intratesticular environment is capable of supporting spermatogenesis, germ cell transplantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 13 publications
1
41
0
Order By: Relevance
“…The cells were pelleted by centrifugation at 600 ϫ g for 5 minutes, after which a single cell suspension was obtained at 34°C by gentle digestion in calcium-and magnesium-free Hanks' balanced salt solution, which contained 0.05 g of collagenase/ml (Life Technologies, Inc., Grand Island, NY), 0.05 mg/ml DNase (Sigma, St. Louis, MO), and 0.025% trypsin (Life Technologies, Inc.). After adding trypsin inhibitor (Sigma), centrifuging, and washing with Dulbecco's modified Eagle medium (Invitrogen Corp. Carlsbad, CA), the cells were then counted, pelleted by centrifugation at 600 ϫ g for 5 minutes, and resuspended in injection media with 0.04% trypan blue stain (Invitrogen Corp.) 1,22 at a concentration of 5 to 15 million cells/ml.…”
Section: Donor Cell Preparation and Transplantationmentioning
confidence: 99%
“…The cells were pelleted by centrifugation at 600 ϫ g for 5 minutes, after which a single cell suspension was obtained at 34°C by gentle digestion in calcium-and magnesium-free Hanks' balanced salt solution, which contained 0.05 g of collagenase/ml (Life Technologies, Inc., Grand Island, NY), 0.05 mg/ml DNase (Sigma, St. Louis, MO), and 0.025% trypsin (Life Technologies, Inc.). After adding trypsin inhibitor (Sigma), centrifuging, and washing with Dulbecco's modified Eagle medium (Invitrogen Corp. Carlsbad, CA), the cells were then counted, pelleted by centrifugation at 600 ϫ g for 5 minutes, and resuspended in injection media with 0.04% trypan blue stain (Invitrogen Corp.) 1,22 at a concentration of 5 to 15 million cells/ml.…”
Section: Donor Cell Preparation and Transplantationmentioning
confidence: 99%
“…When germ cells from jsd animals were injected into W/W V or busulfan-treated recipients, no donorderived spermatogenesis was observed. By contrast, the injection of non-jsd germ cells into jsd recipients demonstrated that jsd animals can support donorderived spermatogenesis for up to seven months 30 . Thus, these data indicate that the jsd phenotype results from a defect in the germ cells, and not in the somatic cells, of the testis.…”
Section: Infertility and Knockout Studiesmentioning
confidence: 93%
“…Another naturally occurring mutation in mice that affects spermatogenesis is the juvenile spermatogonial depletion ( jsd) mutation 30 . This mutation results in mice undergoing a single wave of spermatogenesis, followed by a failure of type A spermatogonial stem cells to repopulate the testis.…”
Section: Infertility and Knockout Studiesmentioning
confidence: 99%
“…In contrast, transplant of wild‐type germ cells into a jsd host leads to full spermatogenesis, confirming that the jsd mutation is an intrinsic problem with the germ cells, and not the somatic environment (Boettger‐Tong et al ., 2000). In a similar approach, transplantation of germ cells from estrogen receptor‐alpha (αERKO) knockout mice, which are infertile, into germ cell‐depleted hosts leads to normal spermatogenesis, showing it is the somatic environment underpinning this particular infertility phenotype (Mahato et al ., 2000).…”
Section: Germ Cellsmentioning
confidence: 99%